Unilateral Uterine Torsion in a Pregnant Cat - Hendy, Eslam Ahmed Abdullah; Elgohary, Bardees Khaled (Journal of Advanced Veterinary Research, 2023)
A 7-year-old female Shirazi cat was referred by a private clinic to the Department clinic of Veterinary Surgery, Anesthesiology and Radiology, Faculty of Veterinary Medicine, Zagazig University with a history of lethargy, anorexia and confirmed pregnancy by ultrasonography. Clinical examination of the case showed acute abdominal pain and abdominal distention with a bloody vaginal discharge. The radiographic image revealed a tubular soft tissue opacity. Upon stabilization of the case surgical approach by exploratory laparotomy to observe a 90o degree twisted left horn, congested blood vessels and dark red, soft, edematous uterine horn. ovariohysterectomy was performed. Fluid therapy and antibiotics were administered, the case survived and regained appetite a few days post-operative with no need for blood transfusion.